A single dose of cannabidiol reduces blood pressure in healthy volunteers in a randomized crossover study - Jadoon, Khalid A.; Tan, Garry D.; O'Sullivan, Saoirse (American Society for Clinical Investigation, 2017)
BACKGROUND. Cannabidiol (CBD) is a nonpsychoactive phytocannabinoid used in multiple sclerosis and intractable epilepsies. Preclinical studies show CBD has numerous cardiovascular benefits, including a reduced blood pressure (BP) response to stress. The aim of this study was to investigate if CBD reduces BP in humans. METHODS. Nine healthy male volunteers were given 600 mg of CBD or placebo in a randomized, placebo-controlled, double-blind, crossover study. Cardiovascular parameters were monitored using a finometer and laser Doppler. RESULTS. CBD reduced resting systolic BP (–6 mmHg; P < 0.05) and stroke volume (–8 ml; P < 0.05), with increased heart rate (HR) and maintained cardiac output. Subjects who had taken CBD had lower BP (–5 mmHg; P < 0.05, especially before and after stress), increased HR (+10 bpm; P < 0.01), decreased stroke volume (–13 ml; P < 0.01), and a blunted forearm skin blood flow response to isometric exercise. In response to cold stress, subjects who had taken CBD had blunted BP (–6 mmHg; P < 0.01) and increased HR (+7 bpm; P < 0.05), with lower total peripheral resistance. CONCLUSIONS. This data shows that acute administration of CBD reduces resting BP and the BP increase to stress in humans, associated with increased HR. These hemodynamic changes should be considered for people taking CBD. Further research is required to establish whether CBD has a role in the treatment of cardiovascular disorders.